Korelasi Penggunaan Aplikasi Raport Digital Terhadap Kinerja Guru SD Negeri di Kelurahan Tuban Tahun Pelajaran 2019-2020 - Rusmayani, Rusmayani; Fahsya, Muhammad Akhid; Khoeron, Khoeron (Faidatuna, 2020)
The Digital Report Card (ARD) application is a web-based application system that is expected to be able to change the work pattern of teachers from manual patterns to digital patterns and is expected to make it easier for teachers to make assessments of students even to print report cards and evaluate the value of student learning outcomes. The objectives of this study are; (1) To find out that there is a relationship between the use of the Digital Report Card Application and the performance of Public SD teachers in Tuban Village, Badung 2019-2020; (2) to find out how much the relationship between the Digital Report Card Application and the performance of Public Elementary School teachers in Kelurahan Tuban, Badung 2019-2020. This research is correlational quantitative which is used with saturated sample method with 46 samples. Data collection techniques used as premiere data, observation and documentation as secondar data is to use questionnaires the data is analyzed with the product moment formula. The results showed that it is known that r count 0.293 is greater than r table 0.291. So that there is a relationship between the use of the digital report card application on teacher performance. If interpreted in the table the value of r, the relationship is low or weak. 2) the digital report card application variable (X) has a contribution of 8.6% to the teacher performance variable (Y) and the rest is 91.4% influenced by other factors not examined in this study.